Impact of Benefit Realization Management on Two-dimensional Model of Project Success: Evidence from Pakistani Telecom Industry - Kazmi, Syed Sibtain; Rafi, Arslan; Hassan, Muhammad (International Review of Management and Marketing, 2016)
This particular research study aims at exploring the role of benefit realization management on two dimensional model of project success. Is there any relation between BRM practices and project success? The population of the current research study is the telecom industry of Pakistan which includes multinational and national companies. Multinational companies are Telenor, Warid and Zong whereas national companies are PTCL, Ufone, and Mobilink. The sample will include employees of above mentioned multinational and national telecom companies. Study confirms that proper implementation of BRM practices (planning, realization, review and strategy) could lead to better project performance in both ways; project management success and product or process success. As far as the project success is concerned, it is a combination of measure of effectiveness and measure of efficiency. Project success is the sum of project efficiency (time, cost and requirement) and project effectiveness (end user satisfaction and return on investment). Measure of efficiency is about cost, time and quality for maximization of output in respect of certain level of input or resources, while effectiveness is about achievement of goals and objectives. Our research was limited to the area of Islamabad Pakistan with a less and specific time frame and respondents. More extensive study could be done in future including other cities and industries. Keywords: Project success, Benefit Realization Management, Telecom Industry, Project Management Success JEL Classifications: J10, M10